2012
DOI: 10.1007/s10571-012-9823-5
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effect of Methylglyoxal on the Intracellular Ca2+ Signaling and Neurite Outgrowth in Mouse Sensory Neurons

Abstract: The formation of advanced glycation end products is one of the major factors involved in diabetic neuropathy, aging, and neurodegenerative diseases. Reactive carbonyl compounds, such as methylglyoxal (MG), play a key role in cross-linking to various proteins in the extracellular matrix, especially in neurons, which have a high rate of oxidative metabolism. The MG effect was tested on dorsal root ganglia primary neurons in cultures from adult male Balb/c mice. Lower MG doses contribute to an increased adherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
4
17
0
1
Order By: Relevance
“…Such promoting effect of carbonyl stress in cancer is inferred for the first time from our data and certainly awaits more comprehensive studies before confirmation. In a non-tumoral context, MG dual effect has been shown recently for neurons where MG is favorable to neurons development and activity while high MG levels are toxic (Radu et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Such promoting effect of carbonyl stress in cancer is inferred for the first time from our data and certainly awaits more comprehensive studies before confirmation. In a non-tumoral context, MG dual effect has been shown recently for neurons where MG is favorable to neurons development and activity while high MG levels are toxic (Radu et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…However, Cai et al [117] demonstrated a biphasic elevation of intracellular Ca 2+ in MDA-incubated (30 min) hippocampal neurons with an early phase assigned to Ca 2+ release from SR via IP 3 R and a late phase from Ca 2+ influx through L-type VDCC. Methylglyoxal-treated (24 h) sensory neurons upon KCl mediated plasma membrane depolarization showed a dual effect on Ca 2+ influx with an increase of intracellular Ca 2+ at low methylglyoxal concentrations (up to 150 µM) and a decrease at higher concentrations (250–750 µM) [118]. Albano et al demonstrated a correlation between elevation of intracellular Ca 2+ and lipid peroxidation in isolated rat hepatocytes stimulated with FeCl 3 [119].…”
Section: Resultsmentioning
confidence: 99%
“…However, we did not observe any changes in neuronal viability with prolonged MG treatment in our DRG cultures, which rules out neuronal cell death as a possible explanation for the effects reported in this study. Other studies have indicated that survival of DRG neurons is decreased after 24 hr of incubation with MG only at concentrations above 750 µM (Radu et al, ).…”
Section: Discussionmentioning
confidence: 96%